Relevance of Higher Education in our Time - Khuramova Farangiz Uchkun kizi (Peerian Journals Publishing, 2022)
The topic of education in the modern world is very relevant. In the modern world, globality is one of the most important parameters of the existence of human society. Reflecting the processes of inter conditionality and interdependence of various components of the world community, globality expresses the ideas of the integrity of all mankind as a sociobiological entity
Keywords: Innovation; education; modernization; educational process